PENGARUH MEKANISME CORPORATE GOVERNANCE, AUDIT TENURE, UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP INTEGRITAS LAPORAN KEUANGAN - Angga Eka Saputra, 12.05.52.0072; Indarti, MG. Kentris (Students' Journal of Accounting and Banking, 2016)
The purpose of this study was to examine and analyze the factors that affect the integrity of the financial statements. Independent variables used in this research is corporate governance, audit tenure, firm size and leverage. While the dependent variable used in this study is the Integrity of Financial Statements. This research was conducted in the Indonesia Stock Exchange using the Corporate Governance Perception Index (CGPI) that have gone public. The population in this research is listed companies in Indonesia Stock Exchange and the Corporate Governance Perception Index (CGPI) in the study period from 2011 until 2014 years. The sampling method using purposive sampling. The influence between variable explained using multiple linear regression test results and test results - t The results showed that the corporate governance affect the integrity of financial statements, audit tenure significant negative effect on the integrity of financial statements, while the size of the company and leverage do not affect the integrity of financial statements.  Keywords: Corporate Governance, Audit Tenure, Firm Size, Leverage, Integrity Of Financial Statements